2020
DOI: 10.1051/epjconf/202023104002
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Reflector Materials for Cold Neutrons

Abstract: Neutron scattering techniques and neutron applications in general are powerful and well-established tools for research in science and technology. However, those are highly intensity-limited techniques and the need to reduce the neutron loses between their source to detection is then an imperative endeavor. In particular, great effort has been devoted to the development of efficient ways to transport and guide neutron beams, as well as to reduce the flux leakage in the non-emitting sides of moderator systems. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Bands between 1090 and 1220 cm −1 correspond to CF 2 and CF 3 symmetric stretch, CF 2 asymmetric stretch, as well as CF=CF 2 , CF 3 -CF 2 and CF stretch vibrations [48]. This latter contribution dominates according to solid-state NMR characterization [12]; CF 2 and CF 3 are not evidenced neither by 19 F nor 13 C measurements. C-F bonds result from both conversion of C-H and COH into C-F in the diamond core and fluorination of sp 2 C in the shell (C exsp 2 -F).…”
Section: Chemical Composition By Naa and Ir Spectroscopymentioning
confidence: 91%
See 1 more Smart Citation
“…Bands between 1090 and 1220 cm −1 correspond to CF 2 and CF 3 symmetric stretch, CF 2 asymmetric stretch, as well as CF=CF 2 , CF 3 -CF 2 and CF stretch vibrations [48]. This latter contribution dominates according to solid-state NMR characterization [12]; CF 2 and CF 3 are not evidenced neither by 19 F nor 13 C measurements. C-F bonds result from both conversion of C-H and COH into C-F in the diamond core and fluorination of sp 2 C in the shell (C exsp 2 -F).…”
Section: Chemical Composition By Naa and Ir Spectroscopymentioning
confidence: 91%
“…DNDs are particularly interesting for improving performance of VCN and CN sources as well as for the loss-limited extraction of slow neutrons from high-radiation zones. This argument motivates further measurements of DND neutron-scattering cross-sections [ 16 , 17 , 18 ] and the inclusion of neutron scattering on DNDs to neutron simulations [ 18 , 19 , 20 ]. These cross-section studies showed the smallness of inelastic scattering and the importance of accounting for clustering and agglomeration of DNDs in the interpretation of neutron-scattering experiments.…”
Section: Introductionmentioning
confidence: 87%
“…Not only can neutrons be reflected from DNDs, but they can also be lost due to the interaction with DNDs in the course of diffusive motion. As neutron losses in raw DNDs are dominated by a small admixture of hydrogen on the surface of DNDs, the removal of hydrogen by fluorination [21][22][23][24][25] is essential for reducing neutron losses.…”
Section: Introductionmentioning
confidence: 99%
“…Scattering cross sections have been studied in detail in references [ 19 , 20 , 21 ], which in particular underlined the importance of clustering/agglomeration of DND powder samples to allow for a proper interpretation of neutron scattering experiments, and the virtual absence of inelastic scattering. Significant efforts have been devoted to including the diffusion of slow neutrons in the DND powders to neutron transport simulations [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%